2016
DOI: 10.3329/updcj.v6i1.29216
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Explore the Relationship between Dental Caries and Weight of the Slum Living Children in Dhaka

Abstract: Background and Objectives:Dental caries or decay is the most significant dental disease of childhood in Bangladesh. It is also reported to affect the anthropometric outcomes of children. So the objective was to assess the relationship between dental decay and weight of the children living in various slum areas of Dhaka, Bangladesh. Methods: A cross-sectional study was conducted among the children in a slum area of Mirpur, Dhaka. The children were selected by using simple random sampling technique. A total of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In Bangladesh, dental caries is a common oro-dental problem [ 29 , 30 , 31 , 32 , 33 ]. Above 40% of children under 5 years old suffer from dental caries [ 34 , 35 , 36 ]. It has been reported that approximately 88% of people between 13–22 years old are missing one or more permanent teeth due to dental caries or related complications [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, dental caries is a common oro-dental problem [ 29 , 30 , 31 , 32 , 33 ]. Above 40% of children under 5 years old suffer from dental caries [ 34 , 35 , 36 ]. It has been reported that approximately 88% of people between 13–22 years old are missing one or more permanent teeth due to dental caries or related complications [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%